Toxoplasma acyl-CoA synthetase TgACS3 is crucial to channel host fatty acids in lipid droplets and for parasite propagation - Sheena Dass; Serena Shunmugam; Sarah Charital; Samuel Duley; Christophe-Sébastien Arnold; Nicholas J. Katris; Pierre Cavaillès; Marie-France Cesbron-Delauw; Yoshiki Yamaryo-Botté; Cyrille Y. Botté (Journal of Lipid Research, 2024)
Apicomplexa comprise important pathogenic parasitic protists that heavily depend on lipid acquisition to survive within their human host cells. Lipid synthesis relies on the incorporation of an essential combination of fatty acids (FAs) either generated by a metabolically adaptable de novo synthesis in the parasite or by scavenging from the host cell. The incorporation of FAs into membrane lipids depends on their obligate metabolic activation by specific enzyme groups, acyl-CoA synthetases (ACSs). Each ACS has its own specificity, so it can fulfill specific metabolic functions. Whilst such functionalities have been well studied in other eukaryotic models, their roles and importance in Apicomplexa are currently very limited, especially for Toxoplasma gondii. Here, we report the identification of seven putative ACSs encoded by the genome of T. gondii (TgACS), which localize to different sub-cellular compartments of the parasite, suggesting exclusive functions. We show that the perinuclear/cytoplasmic TgACS3 regulates the replication and growth of Toxoplasma tachyzoites. Conditional disruption of TgACS3 shows that the enzyme is required for parasite propagation and survival, especially under high host nutrient content. Lipidomic analysis of parasites lacking TgACS3 reveals its role in the activation of host-derived FAs that are used for i) parasite membrane phospholipid and ii) storage triacylglycerol (TAG) syntheses, allowing proper membrane biogenesis of parasite progenies. Altogether, our results reveal the role of TgACS3 as the bulk FA activator for membrane biogenesis allowing intracellular division and survival in T. gondii tachyzoites, further pointing to the importance of ACS and FA metabolism for the parasite.